GADAI MOTOR DESA CINANGSI KECAMATAN CIBOGO KABUPATEN SUBANG MENURUT HUKUM POSITIF DAN HUKUM ISLAM - Sopani, Muhamad; Abbas, Ahmad Sudirman; Fitri, Ahmad Asrof (Journal of Islamic Studies, 2023)
According to positive law and Islamic law, this undergraduate thesis examines motorbike pawning in the village of CAnangsi, Cibogo sub-district, Subang Regency. The main issue with this research is that the system utilized in the practice of pawning in the village of Cinangsi still relies on family and confidence between the pawner and the recipient of the pawn without a clear agreement, raising the possibility of future conflicts. The purpose of this study is to determine, among other things, how the implementation of motorcycle pawning occurred in the village of Cinangsi, how the positive legal and islamic law review of the motorcycle pawn contract in the village of Cinangsi. This study used a qualitative approach with purposive sampling data collection techniques. According to the findings of the study, the pawn contract used in Cinangsi Village does not use a written agreement and instead relies on a mutual trusting attitude. This is contrary to positive law in Indonesia, namely Article 1151 of the Criminal Code because pawn transactions conducted by Chinese citizens are not covered by a pawn agreement. Meanwhile, according to Islamic law, pawning in Cinangsi is not permissible because the pillars and requirements for pawning are not met, specifically the pawn transaction does not set a time restriction for making a pawn contract.